Perbandingan Hasil Belajar Siswa Dengan Menggunakan Model Pembelajaran Course Review Horay Dan Artikulasi Pada Mata Pelajaran Ekonomi - Rijal Lubis; Alkausar Saragih (Universitas Hamzanwadi, 2022)
This research was conducted at SMA 3 Tanjungbalai and this research is also motivated by a condition that is not conducive in the learning process. In this case, using a comparison between the learning model of the course review horay and the articulation learning model to determine the increase in economic learning outcomes in class X of SMA Negeri 3 Tanjungbalai. The purpose of the research is to find out the differences in student learning outcomes on economic subjects using the learning model of the course review horay and those using the learning model of articulation in class X of SMA Negeri 3 Tanjungbalai. The subjects in this study were class X students of SMA 3 Tanjungbalai and a sample of 60 students, in class X IIS 2 there were 32 students (using the course review horay learning model) and class X IIS 4 totaling 28 students (using articulation learning models). The hypothesis of this study is that there are differences in economic learning outcomes of students who are taught using the learning model of the course review horay and articulation learning models. The results of this study indicate that tcount> ttable 2.7125> 2.002 so that there are differences in student learning outcomes on economic subjects taught by using the learning model course review horay and articulation learning models in class X of SMA 3 Tanjungbalai. Based on the average learning outcomes of the experimental class 1 is 80.46. While the average value of the experimental class 2 is 71.78, this means that the learning outcomes of students who are taught using the course review horay learning model are higher than the learning outcomes of students applying the articulation model.